Evaluación del bienestar generado por la aplicación de una prótesis en 3D, a unos pacientes caninos "Canis lupus familiaris" con una extremidad amputada en la ciudad de Latacunga. - Gutiérrez Campaña, Steven Fabián (2022)
At this research report, it was made a 3D prosthesis adapted to measurements of two canine patients, with different amputated limbs, which were printed using 3D technology. The purpose of this research was to make a low cost prosthesis that comply with same functionality as conventional prostheses of the market, in order to solve one of the most remarkable problems, which is the abandonment or euthanasia; this is usually a decision that owners take when they have a dog that finds itself in these physical conditions, for simple fact of expensive and hard-to acquire prostheses. The first thing done was taking measurements of each patient, as a reference its other limb, with the use of the tape measure; once measurements were obtained, the prototypes were drawn, to underline possible prostheses that could use patients, and with these specifications, with the use of the "Blender” program, each prototype was digitalized. According to established measures. Once this process was finished it was proceeded to print, using a 3D printing machine; each prosthesis had a duration of 7 to 14 printing hours. Once printed is proceeded to place the prosthesis to each patient, and evaluate their adaptability and stress; for this purpose, we used cortisol as a stress biomarker and thus through a blood sample of each patient, obtain the final results. The importance of this project was to evaluate each patient, if the prosthesis was useful, or simply caused discomfort, pain and stress, in order to be able to benefit more dogs in the same physical conditions in the future and to help them. The impacts generated by this research are very noticeable, on environmental field, since its residues are biodegradable and reusable; on economic field since it is a low-budget prosthesis affordable by any person; in the social field, by creating a social project to help physically disabled animals; and finally in the technical field, by creating a strong and functional prosthesis.